Anti-reflux surgical treatment for Barrett’s oesophagus - B. F. Shevchenko; N. V. Prolom; O. M. Babii; S. O. Tarabarov; O. V. Zeleniuk (Zaporožskij Medicinskij Žurnal)
The aim of the study. To improve the effectiveness of surgical treatment for patients with hiatal hernia (HH) and gastro-esophageal reflux disease (GERD) in combination with Barrett’s esophagus by developing a new method for surgical correction of the physiological cardia incompetence.